Response due to concentrated force in micropolar elastic solid with voids - Singh, R.; Singh, K. (Zielona Góra: Uniwersytet Zielonogórski)
The eigen value approach, following Laplace and Fourier transforms has been employed to find the general solution of the field equation in a micropolar elastic solid with voids for the plane strain problem. An application of an infinite space with impulsive force has been taken to illustrate the utility of the approach. The integral transformations have been inverted by using a numerical inversion technique to get result in physical domain. The result in the form of normal displacement, volume fraction, normal force stress, tangential force stress and tangential couple stress components has been obtained numerically and illustrated graphically to depict the effect of micropolarity and voids.
Keywords: eigen value; voids; Laplace and Fourier transform; concentrated force; Romberg`s integration